Effects of Dietary-SCFA on Microbial Protein Synthesis and Urinal Urea-N Excretion Are Related to Microbiota Diversity in Rumen - Lu, Zhongyan; Shen, Hong; Shen, Zanming (Frontiers in Physiology, 2019)
Two experiments were performed in this study. In Experiment 1, twenty goats were fed with an isonitrogenous diet, containing 28% Non-Fiber Carbohydrate (MNFC group, n = 10) or 14% NFC (LNFC group, n = 10). In the MNFC group, the ruminal concentration of Short Chain Fatty Acids (SCFA) increased, and pH declined. Compared with those in the LNFC group, the microbial protein synthesis in rumen and mRNA abundance of urea transporter B (UT-B) in rumen epithelium increased in the MNFC group, although serum urea-N (SUN) did not differ significantly between groups. Simultaneously, urinal urea-N excretion was reduced in the MNFC group. Significant correlations were found between rumen SCFA and UT-B and between UT-B and urinal urea-N excretion. Furthermore, the abundances of SCFA receptor of GPR41 and GPR43 increased in the rumen epithelium of the MNFC group. These results suggest that increases of SUN transported into the rumen and incorporated into microbial protein and decreases of urinal urea-N excretion are related to ruminal SCFA. This is supported by data from our previous study in which added SCFA on the mucosal side caused increases of urea transport rate (flux Jsm urea) from the blood to the ruminal lumen side. In Experiment 2, we used 16S rRNA Amplicon Sequencing to analyze the structure of the ruminal microbiota community in relation to SCFA. An additional eight goats were assigned into the MNFC (n = 4) and LNFC (n = 4) groups. The dietary ingredients, chemical composition, and feeding regimes were the same as those in Experiment 1. Constrained correspondence analysis (CCA analysis) revealed NFC promoted the expansion of microbiota diversity, particularly of SCFA-producing microbes. The function prediction of 19 upregulated Kyoto Encyclopedia of Genes and Genomes (KEGG) ortholog groups showed an NFC-induced increase of the types and abundances of genes coding for enzymes catalyzing N and fatty acid metabolism. Based on our present and previous investigations, our results indicate that, in goats consuming a MNFC diet, the facilitated urea transport in the rumen and improved urea N salvage are triggered by an expansion of ruminal microbiota diversity and are signaled by ruminal SCFA. This study thus provides new insights into the microbiota involved in the dietary modulation of urea-N salvage in ruminant animals.